A Phenomenological Study exploring Healthcare Workers‟ Experiences of Nutrition and Mealtimes in Hospitalised Older Patients - Howarth, Rachel Helen (2012)
Background: A recent report from the Care Quality Commission showed that 20% of hospitals do not meet the required standards for dignity and nutrition whilst 35% need to make improvements (CQC, 2010). Older people are particularly at risk of malnutrition due to a natural decline in their physiological state and the influence of social and psychological factors. Malnutrition can have serious consequences for older people, often escalating existing health problems and has been linked to an increase in hospital stay and even death. Aim: To explore the attitudes, opinions and experiences of healthcare workers towards nutritional care of the older hospitalised patient. Method: An interpretive phenomenological approach was used. Therefore, the study was concerned with the „lived experiences‟ of the participants. The participants were healthcare workers from a healthcare of the older person ward. Data was collected using semi-structured interviews which were audio recorded and then transcribed. The interviews were analysed using thematic analysis in order to draw out themes. Findings: The healthcare workers showed a positive attitude towards nutritional care of the older person. They wanted to protect their patients from malnutrition which was indicated by the detailed description of their responsibilities at mealtimes and their use of nutritional tools such as nutritional assessment, red trays and protected mealtimes. However, they identified barriers which hindered them in protecting their patient; lack of education and training, busyness, hospital systems and bad press. Conclusion: The healthcare workers wanted to protect their patients from malnutrition but they were limited from doing this efficiently by specific barriers. Recommendations for practice were made on the basis of the findings. These were improving training, reducing conflicting pressures at mealtimes, ensuring adequate staffing levels and changing hospital systems for ordering food.